An Application of Data Envelopment Analysis and Game Theory for Appraisal of Balanced Scorecard Indexes in Media Industry - Taherinezhad, Ali; Alinezhad, Alireza; Gholami, Saber (Journal of Industrial System Engineering and Management, 2023)
Todays, the media industry encompasses all businesses that allow information to be shared (traditional and digital media). Media is vast, large, and ever-growing, and is an incredibly popular sector at the minute, and an extremely interesting area to research work in. This paper considered a news agency of media organization as a Decision-Making Unit (DMU). The aim of the study was to evaluate the role of Balanced Scorecard (BSC) indexes on measuring the efficiency of DMU. This was done by a new hybrid model of Data Envelopment Analysis (DEA), cooperative game theory and Shapley value index. The initial values of the DEA model were selected from among the BSC indexes in four perspectives (i.e., financial, customer, internal processes, and growth and learning). Finally, the proposed model was experimented on a case study and the computational results were obtained. The results showed that the profitability ratio with a Shapley value of 2.903 and the percentage of satisfied audiences with a Shapley value of 0.404 had the highest and lowest reflection in performance assessment, respectively. The rest of the results were presented and discussed in detail. This study can reveal scientific orientation to increase organizational performance to media managers and policymakers.